2016
DOI: 10.1002/nha3.20135
|View full text |Cite
|
Sign up to set email alerts
|

Why Go Back to School? Investigating the Motivations of Student Parents to Pursue Post-Secondary Education

Abstract: This study explored the factors that motivate student parents to pursue post‐secondary education. Student parents at four Canadian universities (n=398) completed open‐ended questions on their reasons for attending school in an online survey. Using Possible Selves Theory as a lens, we conducted a directed content analysis and found that student parents’ motivation to attend school has a strong future orientation. Primary motivators for engaging in post‐secondary study included: to attain a valued job/career, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In fact, the Institute for Women’s Policy Research recently reported that at least 2.1 million students—or 11% of all undergraduates—are raising children (Gault, Milli, & Cruse, 2018). Findings from the Mature Student Experience Survey—a 3-year study of undergraduate students aged 25 years and older—revealed that student-parents’ motivations for pursuing a college career are varied and include reasons related to professional and educational success as well as family and relationships (van Rhijn, Lero, & Burke, 2016).…”
mentioning
confidence: 99%
“…In fact, the Institute for Women’s Policy Research recently reported that at least 2.1 million students—or 11% of all undergraduates—are raising children (Gault, Milli, & Cruse, 2018). Findings from the Mature Student Experience Survey—a 3-year study of undergraduate students aged 25 years and older—revealed that student-parents’ motivations for pursuing a college career are varied and include reasons related to professional and educational success as well as family and relationships (van Rhijn, Lero, & Burke, 2016).…”
mentioning
confidence: 99%
“…The relationship between years of work experience and motivation confirms the notion that as adults age and their children (if they have any) become independent, adults tend to become more extrinsically motivated. While previous research on adult learners suggests adults are motivated for varied and complex reasons, as adult learners spend more time in the workforce, they become more extrinsically oriented (Rhijn et al, 2016). Kyndt et al (2011) found a decrease in motivation to learn as one ages.…”
Section: Intersectionality Theorymentioning
confidence: 80%
“…Patton (2002) also suggests the use of multiple methods for experiencing lower levels of employer-sponsored support. Employers interested in retaining aging adults who, by nature of years "on the job" grow more extrinsically motivated (Rhijn et al, 2016), might consider offering continued education through an employee benefits programs, providing a valuable intrinsically motivating retention strategy.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Another study by Waters & Lemon (2019) regarding the assessment of the underlying motivations of first-year mature students in Australia revealed that motivations in the mature students are seen throughout the initial year and is changed constructively as the student transits to the next advanced level semester. Furthermore, earning higher income after acquiring HE skills through an advanced certification/degree and/or enhancing one's learning through active engagement at college are other motivational factors in older students to make their future bright (Rhijn, et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%